Effectiveness Use Application Screen Reader To Improve The Independence Of Blind People With Disabilities In Pertuni, Bengkulu City - Rinku Yendriansyah; Ishak Fadlurrohim; Iqbal Rahmat Gani (Utan Kayu Publishing, 2026)
This study discusses how screen reader applications help visually impaired people in Bengkulu City in carrying out their daily activities and increasing their independence. The study was conducted qualitatively by involving ten informants who are active members of PERTUNI. They have been using screen readers for at least six months and are accustomed to interacting with this technology in their daily activities. The results show that screen readers not only help them achieve their initial goals of use, such as working, communicating, or accessing social media, but also strengthen social relationships and improve their ability to adapt to technology. Although some informants experienced difficulties at the beginning of use because they had never used a smartphone, they were still able to adapt with the support of their families and environment. In terms of independence, screen readers made the informants more confident in making decisions, managing their personal lives, and carrying out activities without relying heavily on others. Thus, it can be concluded that screen readers are a very useful technology for people with visual impairments because they help them live more independent and empowered lives